Substernal multinodular goiter together with brainstem pathology: Misleading manifestations - (:unkn) unknown (My University, 2001)
This study aimed at analyzing the clinical presentation, diagnosis, management and results of the treatment of substernal multinodular goiter. Substernal goiter with its clinical presentation can be misdiagnosed. When a patient with substernal multinodular goiter is presented with symptoms like dysphagia, hoarseness and dyspnea, while ruling out the possible malignant or benign causes, central cranial system originated pathologies should always be kept in mind.
Keywords: Brainstem pathology; Dysphagia; Dyspnea; Hoarseness; Substernal goiter